(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This means ensuring tourist destinations, products and services are accessible to all people, regardless of their physical limitations, disabilities or age. Accessible tourism aims to allow tourism destinations to be enjoyed equally by everyone.